Bioavailable IGF-1 is beneficially associated with biomarkers of endothelial function in young healthy adults: The African-PREDICT study. (August 2018) - Barnard, Sunelle A.; Smith, Wayne; Mels, Catharina M.C.; Botha, Shani; Schutte, Aletta E.
Abstract: Introduction: Low circulating levels of insulin-like growth factor-1 (IGF-1) are associated with endothelial dysfunction, subsequently leading to the development of cardiovascular disease. Objective: To better understand the early phases of vascular deterioration in a young, healthy population, we investigated, cross-sectionally, whether biomarkers of endothelial function (intercellular adhesion molecule-1 (ICAM-1), vascular cell adhesion molecule-1 (VCAM-1) and von Willebrand factor antigen (vWFag )) are associated with IGF-1 in a healthy study population forming part of the larger African Prospective study on the Early Detection and Identification of Cardiovascular diseases and Hypertension (African-PREDICT). Method: We included 825 black and white men and women (aged 20–30 years) and determined IGF-1, IGF binding protein-3 (IGFBP-3), ICAM-1, VCAM-1 and vWFag from blood samples. We also measured 24-h blood pressure and health behaviours namely waist circumference, accelerometery, cotinine and gamma glutamyl transferase. We used the IGF-1/IGFBP-3 M ratio as an estimate of bioavailable IGF-1. Results: In multivariable-adjusted regression analyses performed in the total group, VCAM-1 associated positively with IGFBP-3 (β = 0.21; p < .001) and negatively with IGF-1/IGFBP-3 (β = −0.18; p < .001). ICAM-1 showed a borderline negative association with IGF-1 (β = −0.09; p = .054) and IGF-1/IGFBP-3 (β = −0.08; p = .057). vWFag was not associated with IGF-1, IGFBP-3 or bioavailable IGF-1. Conclusion: VCAM-1 is beneficially associated with IGF-1 in a young healthy cohort, independent of sex, ethnicity, blood pressure and health behaviours – thereby confirming the potential importance of bioavailable IGF-1 in early vascular endothelial protection. Highlights: Role of IGF-1 in early phases of cardiovascular disease development unclear. In young adults we found IGF-1 linked inversely to endothelial activation. Our findings support the role of IGF-1 in early vascular endothelial protection.